Obesity in Pregnancy – Implications on Pregnancy Events - Koleva, Lilia; Spasova, Victoria; Popova, Marieta; Petkova, Valentina; Dimitrov, Milen (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Overweight and obesity are serious health problems in most developed countries. The percentage of young women with excessive weight who get pregnant continues to grow every year. This raises a concern about the risks of the mother and the baby during pregnancy and after birth. AIM: This study aims to determine health risk for overweight mothers and especially the risk for preterm birth. MATERIALS AND METHODS: This is a prospective and retrospective study taking place in the outpatient clinic of the University Hospital “Maichin Dom”. Our study included 105 pregnant women with BMI ≥25 kg/m2 as a case group and 91 pregnant women with BMI within normal limits as a control group. RESULTS: Mean BMI in the case group was 34.79 ± 3.71 kg/m2 and 20.20 ± 2.24 kg/m2 in the control group. Among 105 women in the case group, we registered 24.8% (n = 26) who gave birth before term. Preterm births among 91 women in the control group were registered in 17.6% (n = 16) patients. We found a significant correlation between increased BMI and the risk of increased systolic and diastolic blood pressure. Moreover, we found comorbidities in 43.8% of cases and 24.2% of controls. CONCLUSION: Maternal overweight and obesity during pregnancy are associated with increased risks of preterm delivery and complications of pregnancy. Extra efforts should be made to help women lose weight before this important period of life.